KERJASAMA EL SALVADOR DENGAN AMERIKA SERIKAT DALAM MENANGGULANGI KEJAHATAN LINTAS BATAS KELOMPOK KRIMINAL BERSENJATA MARA SALVATRUCHA (MS-13) TAHUN 2017-2021 - Suci Wandani; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study describes the security cooperation between El Salvador and the United States of America to countermeasure transnational crimes committed by armed criminal groups, especially criminal groups with the greatest influence and the most criminal cases in the Americas, namely the MS-13 (Mara Salvatrucha). The crimes committed by MS-13 include the mass murder on Long Island in 2017 and several cases of extortion in several suburbs of San Salvador. The transnational crimes committed by MS-13 is reported have sparked fear in society and have been regarded as the public enemy and caused suffering to a very high degree of violence for the people of El Salvador and the United States. The author collects data from books, academic journals, official documents, theses and sources from the internet related to the research issue of El Salvador's cooperation with the United States in countermeasure transnational crime by MS-13. The author uses the perspective of neorealism and state level analysis. While the theory used in this theory is the theory of international cooperation. The results show that the collaboration between El Salvador and the United States of America, namely several security operations under the Operation Community Shield program between 2017-2021 resulted in great success in increasing security in El Salvador and the United States by arresting more than 700 leaders and 11,000 members of armed criminal groups MS-13. The government authorities of El Salvador and the United States have also managed to solve more than 50 cases of murder and violence, disrupt the financial system of armed criminal groups MS-13, shut down dozens of illicit businesses, and confiscate hundreds of assets of MS-13. Keywords: Armed Criminal Group, MS-13, International Cooperation, Armed Violence, Transnational Crimes.